Effects of different conditions tested "in vitro" on the phosphorus runoff potential of livestock manure. (15th June 2022) - Xu, Fuqing; Ma, Hongzhen; Liang, Jiawei; Okopi, Solomon Inalegwu; Yang, Shoujun; Cao, Leipeng; Sun, Weimin
Highlights: Effects of manure long-term storage (150–180 days) on WEP (P runoff potential) was studied. WEP increased significantly in the first 15–30 days then decreased. Aerobic conditions and higher temperatures enhanced WEP reduction. Manure stored for less than 30 days had the highest P runoff potential. Long-term storage achieved 90%±3% and 71%±5% WEP reduction for swine and dairy manure. Abstract: This study aimed to investigate the changes of swine and dairy manure characteristics during a long-term storage (150–180 days) under 4 °C, 20 °C, and 37 °C, sealed and unsealed conditions. Water extractable phosphorus (WEP) of both manures rapidly increased during the first 15–30 days and then decreased. At the end of the storage, the WEP reduction was 90%±3% and 71%±5% of the initial concentration for swine manure and dairy manure, respectively. Generally, unsealed storage and higher temperatures led to more WEP reduction. This study suggested that manure stored for less than 30 days had the highest P runoff potential, while a long-term manure storage reduced P runoff potential compared to freshly excreted manure.